SYNTHESIS AND OPTICAL PROPERTIES OF NITROGEN-DOPED CARBON QUANTUM DOTS - Thi Kim Dung, Le; Vinh Phu, Nguyen; Nhu Y, Nguyen; Minh Hoa, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Nitrogen-doped carbon quantum dots (N-CQDs) were successfully synthesized using a hydrothermal method at 150°C for 3 hours, with glucose and urea serving as the carbon and nitrogen precursors, respectively. The resulting N-CQDs, which had an average particle size of 3.60 ± 0.57 nm, exhibited blue fluorescence with an emission peak approximated 485.5 nm when excited at 370 nm. The photoluminescence intensity of the N-CQDs was pH-dependent, reaching its maximum at pH 5.0. Fourier transform infrared spectroscopy analysis revealed that the surface of the N-CQDs contained functional groups with carbon, nitrogen, and oxygen bonds, which contributed to their excellent water solubility and strong blue photoluminescence (quantum yield of 23%). These properties indicate that N-CQDs have high potential for applications in bioimaging and biosensing.